Formulation And Evaluation Of Hydrotropic Solublization Based Suspensions Of Griseofulvin - DR.B.ANILREDDY (International Journal of Pharma and Bio Sciences, 2010)
Hydrotropes increases the solubility of organics in water. Objective of present investigation was to enhance the solubility of griseofulvin using the technique of hydrotropic solubilization technique and convert them into suitable oral liquid dosage form (suspension) useful for enhancement of bioavailability. 0.5M, 1M, 2M of the hydrotropes (tri sodium citrate, urea, sodium acetate, sodium benzoate and sodium salicylates) were used to study the saturation solubility. Solubility was found to be greater with sodium benzoate. Suspensions were prepared by using sodium benzoate solution, greseofulvin, xanthan gum, acacia, sodium alginate as a aqueous phase, dispersed phase and suspending agents respectively. Prepared suspensions were characterized for appearance of phases, density, particle size of dispersed Phase, pourability, sedimentation volume and invitro drug release. All formulations of sodium benzoate suspension were uniformly distributed, density in the range of 1.020 to 1.050gm/ml, particle size of the dispersed phase was 10µm to 20µm, suspensions were easily pourable from the bottle and sedimentation volume was in the rage of 0.5-1. More than 70% drug release was obtained at the end of the 45 minutes. Hydrotropic solublization technique for preparation of suspensions of poor water soluble drugs will gave stability to the formulation and helps in enhancement of bioavailability of greseofulvin.